Negative electrode slurry and preparation method thereof, negative electrode plate and lithium ion battery
Through the combination of hard silicon-based particles and conductive agents, a uniform three-dimensional conductive network is formed, which solves the problem that the conductive network in lithium-ion batteries is susceptible to stress and improves the cycling and rate performance of the battery.
Patent Information
- Application Number
- CN202411130308.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-15
- Publication Date
- 2024-12-27
AI Technical Summary
The conductive network of silicon-based electrodes in lithium-ion batteries is susceptible to stress concentration during the cycle process, resulting in uneven charge distribution and secondary agglomeration of conductive agents, affecting the cycling and rate performance of the battery.
Using a combination of hard silicon-based particles, particulate conductive agent and linear conductive agent, the secondary agglomeration of conductive agents is suppressed through mutual collision between hard silicon-based particles, forming a uniform three-dimensional conductive network, improving conductive properties and reducing conductivity Dosage.
The uniform dispersion of the negative electrode slurry in lithium-ion batteries is achieved, the conductive performance is improved, the cycle life of the battery is extended, and the rate performance is improved.
Smart Images

Figure HDA0004997641210000011 
Figure HDA0004997641210000012 
Figure HDA0004997641210000021
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to negative electrode slurry and a preparation method thereof, a negative electrode sheet and a lithium ion battery. Background Art
[0002] Lithium-ion batteries have become the most commonly used energy storage devices in most electronic products due to their high energy density, from various portable devices to electric vehicles. However, with the development of lithium-ion batteries, the demand for battery life is also increasing. Silicon has the advantages of high theoretical specific capacity, low working potential, and abundant sources, making it a promising negative electrode material for lithium-ion batteries. However, there are two challenges in the practical application of silicon-based electrodes: first, the poor intrinsic conductivity of silicon usually leads to uneven charge distribution throughout the electrode and limited utilization of active materials; second, during the lithium insertion / delithiation reaction, the volume change of silicon (>300%) is very large, resulting in severe stress concentration, which usually causes the silicon particles to shatter and disconnect from the conductive network, resulting in rapid capacity decay in a few cycles. Therefore, building a stable conductive network in silicon-based electrodes is crucial for practical applications.
[0003] At present, the commonly used conductive agents for lithium-ion batteries include zero-dimensional granular conductive agents such as Super P, Ketjen black, and acetylene black, and one-dimensional linear conductive agents such as carbon nanotubes and carbon fibers. The granular conductive agent and the silicon-based particles are in rigid point-to-point contact, and the interface interaction between the non-polar surface of the granular conductive agent and the polar surface of the silicon-based material does not match, that is, the interface contact between the granular conductive agent and the silicon-based negative electrode is very weak, so the conductive network will be damaged in multiple repeated cycles. In addition, the granular conductive agent is very easy to reunite due to the van der Waals force during the slurry preparation process, resulting in an uneven conductive network. The linear conductive agent and the silicon-based negative electrode are in point-line contact, and the carbon nanotubes in the linear conductive agent have a one-dimensional structure, among which the carbon nanotubes with a high aspect ratio can construct a long-range conductive network in the silicon-based negative electrode. However, the carbon nanotubes are easily agglomerated into bundles due to the van der Waals force and have poor dispersion. It can be seen that the conductive agent is prone to secondary agglomeration, resulting in uneven dispersion with the silicon-based particles. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, one object of the present invention is to provide a negative electrode slurry in which the components are dispersed more evenly, which can effectively avoid the problem of secondary agglomeration of the conductive agent during the preparation of the slurry.
[0005] In one aspect of the present invention, the present invention provides a negative electrode slurry. According to an embodiment of the present invention, the negative electrode slurry comprises: hard silicon-based particles, a granular conductive agent, a linear conductive agent, a binder and a solvent, wherein the hardness of the hard silicon-based particles is 50HV to 200HV. Therefore, the negative electrode slurry has a better dispersion system. Specifically, by using the hard silicon-based particles of the above hardness in the negative electrode slurry, in the process of preparing the negative electrode slurry, the mutual collision between the hard silicon-based particles can effectively inhibit the secondary agglomeration of the granular conductive agent caused by the van der Waals force, or the mutual collision between the hard silicon-based particles can knock and scatter the granular conductive agent that has undergone secondary agglomeration, thereby making the granular conductive agent uniformly adhere to the surface of the linear conductive agent, and the granular conductive agent and the linear conductive agent both form a uniform phase wrapped on the surface of the hard silicon-based particles, thereby forming a uniform three-dimensional conductive network, improving the conductive performance of the negative electrode slurry, and effectively inhibiting the expansion of the hard silicon-based particles at the same time; and since the agglomeration of the granular conductive agent is avoided, a small amount of conductive agent can be used to wrap the surface of the hard silicon-based particles, that is, the above technical scheme of the present invention can further reduce the amount of conductive agent used, realize a slurry dispersion system with a low content and high coverage of the linear conductive agent, and at the same time improve the cycle, rate and other performances of the lithium ion battery using the negative electrode slurry.
[0006] According to an embodiment of the present invention, the particle size D50 of the hard silicon-based particles is 3 μm to 10 μm.
[0007] According to an embodiment of the present invention, the mass ratio of the hard silicon-based particles, the granular conductive agent, the linear conductive agent, and the binder is (80-98): (0.05-10): (0.001-1): (1-20).
[0008] According to an embodiment of the present invention, the hard silicon-based particles are spherical or quasi-spherical.
[0009] According to an embodiment of the present invention, the hard silicon-based particles include SiO x @C, Si@C, Si / C, micron Si, SiO, and new silicon carbon; the granular conductive agent includes at least one of Super P, Ketjen black, acetylene black and graphite; the linear conductive agent includes at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes; the solvent is at least one of water or NMP.
[0010] In another aspect of the present invention, the present invention provides a method for preparing the negative electrode slurry described above. According to an embodiment of the present invention, the method for preparing the negative electrode slurry comprises: first mixing hard silicon-based particles, a granular conductive agent, a linear conductive agent, a binder and a solvent to obtain a mixed slurry; and second mixing the mixed slurry under a predetermined pressure to obtain the negative electrode slurry. Thus, the above method can prepare a homogeneous negative electrode slurry. Specifically, during the second mixing process of the mixed slurry, the mutual collision between the hard silicon-based particles can effectively inhibit the secondary agglomeration of the granular conductive agent caused by the van der Waals force, or the mutual collision between the hard silicon-based particles can knock and scatter the granular conductive agent that has undergone secondary agglomeration, thereby making the granular conductive agent uniformly adhere to the surface of the linear conductive agent. The granular conductive agent and the linear conductive agent both form a homogeneous phase wrapped on the surface of the hard silicon-based particles, thereby forming a uniform three-dimensional conductive network, improving the conductive properties of the negative electrode slurry, and effectively inhibiting the expansion of the hard silicon-based particles at the same time; and since the agglomeration of the granular conductive agent is avoided, a small amount of conductive agent can be used to wrap the surface of the hard silicon-based particles, that is, the above technical scheme of the present invention can further reduce the amount of conductive agent used, while improving the cycle, rate and other performances of the lithium-ion battery using the negative electrode slurry. Furthermore, the above method is simple and easy to implement, has high efficiency, and is convenient for industrial production and management.
[0011] According to an embodiment of the present invention, the predetermined pressure is 3000psi to 30000psi.
[0012] According to an embodiment of the present invention, the solid content of the mixed slurry is 25% to 60%.
[0013] According to an embodiment of the present invention, the method for obtaining the mixed slurry includes: preparing the linear conductive agent into a linear conductive slurry; mixing the binder and the solvent to prepare a binder glue; mixing and stirring the hard silicon-based particles, the granular conductive agent, the linear conductive slurry, the binder glue and the solvent to obtain the mixed slurry.
[0014] According to an embodiment of the present invention, the linear conductive agent includes at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes, wherein, in the linear conductive paste, the average length of the single-walled carbon nanotubes is 5μm to 15μm, and the average length of the multi-walled carbon nanotubes is 5μm to 30μm.
[0015] In another aspect of the present invention, the present invention provides a negative electrode sheet. According to an embodiment of the present invention, the negative electrode sheet is prepared from the negative electrode slurry described above. Therefore, the negative electrode sheet of the present invention has good conductivity, which helps to improve the cycle, rate and other performances of the lithium ion battery using the negative electrode sheet. It can be understood by those skilled in the art that the negative electrode sheet has all the features and advantages of the negative electrode slurry described above, and no further elaboration is given here.
[0016] In another aspect of the present invention, the present invention provides a lithium ion battery. According to an embodiment of the present invention, the lithium ion battery includes the negative electrode sheet described above. Therefore, the lithium ion battery of the present invention has better cycle and rate performance. It can be understood by those skilled in the art that the lithium ion battery has all the features and advantages of the negative electrode slurry described above, and no further details will be given here. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0018] Figure 1 This is a SEM image of the electrode sheet after coating with the silicon-based negative electrode slurry prepared in Example 1 of the present invention.
[0019] Figure 2 This is a SEM image of the electrode sheet after coating with the silicon-based negative electrode slurry prepared in Comparative Example 1 of the present invention.
[0020] Figure 3 It is a schematic diagram of the cycle performance test results of button-type batteries assembled with electrode sheets coated with two silicon-based negative electrode slurries prepared in Example 1 of the present invention and Comparative Example 1.
[0021] Figure 4 It is a schematic diagram of the rate performance test results of button-type batteries assembled with electrode sheets coated with two silicon-based negative electrode slurries prepared in Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0022] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.
[0023] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0024] In one aspect of the present invention, the present invention provides a negative electrode slurry. According to an embodiment of the present invention, the negative electrode slurry comprises: hard silicon-based particles, a granular conductive agent, a linear conductive agent, a binder and a solvent, and the hardness of the hard silicon-based particles is 50HV to 200HV. Therefore, the negative electrode slurry has a better dispersion system. Specifically, by using the hard silicon-based particles of the above hardness in the negative electrode slurry, in the process of preparing the negative electrode slurry, the mutual collision between the hard silicon-based particles can effectively inhibit the secondary agglomeration of the granular conductive agent caused by the van der Waals force, or the mutual collision between the hard silicon-based particles can knock and disperse the granular conductive agent that has undergone secondary agglomeration, thereby making the granular conductive agent uniformly adhere to the surface of the linear conductive agent, and the granular conductive agent and the linear conductive agent both form a uniform phase wrapped on the surface of the hard silicon-based particles, thereby forming a uniform three-dimensional conductive network, improving the conductive performance of the negative electrode slurry, and at the same time effectively solving the volume expansion problem of the hard silicon-based particles; and since the agglomeration of the granular conductive agent is avoided, a small amount of conductive agent can be used to wrap the surface of the hard silicon-based particles, that is, the above technical solution of the present invention can further reduce the amount of conductive agent used, and realize a slurry dispersion system with a low content of conductive agent and a high coverage rate, thereby improving the cycle, rate and other performances of the lithium-ion battery using the negative electrode slurry.
[0025] Among them, the hardness of the hard silicon-based particles is 50HV to 200HV, specifically 50HV, 60HV, 70HV, 80HV, 90HV, 100HV, 110HV, 120HV, 130HV, 140HV, 150HV, 160HV, 170HV, 180HV, 190HV, 200HV, etc. Within the above hardness range, the hard silicon-based particles can effectively collide and disperse the granular conductive agent to avoid secondary agglomeration, thereby improving the dispersion of the granular conductive agent. Uniformity helps to improve the conductivity of the negative electrode sheet; if the hardness of the hard silicon-based particles is less than 50HV, the collision force of the hard silicon-based particles during mixing is relatively weak, and the secondary agglomerated granular conductive agent cannot be dispersed well, so that some granular conductive agent still undergoes secondary agglomeration; if the hardness of the hard silicon-based particles is greater than 200HV, the collision force of the hard silicon-based particles during mixing is relatively large, which can easily cause damage to the hard silicon-based particles during the mixing process, resulting in the undesirable phenomenon that the performance of the hard silicon-based particles is not fully exerted.
[0026] According to some embodiments of the present invention, the hard silicon-based particles include SiO xAt least one of @C (carbon-coated oxygen-modified silicon oxide material, where x is a positive number), Si@C (carbon-coated silicon material), Si / C (silicon-carbon composite material), micron Si, SiO, and new silicon-carbon. The silicon-based particles are not only well suited for preparing negative electrode sheets with good conductivity, but also have good hardness, which is helpful for preparing the negative electrode slurry with good dispersibility and good conductivity required by the present invention; in addition, the materials are widely available, easy to purchase or prepare, and have a high cost-effectiveness.
[0027] According to some embodiments of the present invention, the particle size D50 of the hard silicon-based particles is 3 μm to 10 μm, such as 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, etc. The hard silicon-based particles of the above particle size can effectively impact and disperse the particles that are pre-agglomerated for secondary agglomeration, and the hard silicon-based particles of the above particle size are also conducive to their uniform dispersion in the negative electrode slurry, improve the conductivity of the prepared negative electrode sheet, and are also conducive to the coating of the negative electrode slurry to prepare a negative electrode sheet with good performance.
[0028] According to some embodiments of the present invention, the hard silicon-based particles are spherical or quasi-spherical, and thus, the spherical or quasi-spherical hard silicon-based particles have good sphericity, good wear resistance, high mechanical strength, and high-density collision sites, that is, the collision efficiency of the hard silicon-based particles is higher, and the spherical or quasi-spherical hard silicon-based particles have small flow resistance and faster flow speed per unit time, which further improves the collision efficiency between the hard silicon-based particles, thereby improving the production efficiency and dispersion uniformity of the negative electrode slurry. It should be noted that the above-mentioned "quasi-spherical" means that the shape of the hard silicon-based particles is similar to that of a sphere, but may not be a completely perfect sphere.
[0029] According to some embodiments of the present invention, the granular conductive agent includes at least one of Super P, Ketjen black, acetylene black and graphite. The conductive agent has good conductivity, can effectively improve the conductivity of the negative electrode sheet, and has better dispersibility under the collision of hard silicon-based particles, can be well adhered to the surface of the linear conductive agent, and has a wide range of raw material sources, low cost and high cost performance.
[0030] According to some embodiments of the present invention, the linear conductive agent includes at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes. As a result, the carbon nanotubes have a certain degree of flexibility. After the granular conductive agent is attached to the surface of the linear conductive agent, the granular conductive agent and the linear conductive agent form a uniform phase wrapped on the surface of the hard silicon-based particles, which can not only form a uniform three-dimensional conductive network and improve the conductive performance of the negative electrode slurry, but also effectively improve the stress caused by the volume change of the hard silicon-based particles, thereby minimizing the pulverization of the silicon-based particles. Among them, multi-walled carbon nanotubes refer to carbon nanotubes that are greater than or equal to double-walled carbon nanotubes, such as double-walled carbon nanotubes, triple-walled carbon nanotubes, four-walled carbon nanotubes, etc.
[0031] According to some embodiments of the present invention, the binder includes at least one of sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, and polyacrylate. According to some embodiments of the present invention, the solvent is water. Thus, the overall performance of the negative electrode slurry and the negative electrode sheet prepared therefrom can be improved.
[0032] According to some embodiments of the present invention, the mass ratio of the hard silicon-based particles, the granular conductive agent, the linear conductive agent, and the binder is (80-98): (0.05-10): (0.001-1): (1-20). For example, the mass ratio of the hard silicon-based particles, the granular conductive agent, the linear conductive agent, and the binder is 80:9.95:0.05:10, 85:4.9:0.1:10, 90:4.9:0.1:5, 95:1.995:0.005:3, etc. The above ratios The negative electrode slurry obtained in the example has good uniformity, and the negative electrode sheet prepared therefrom has an excellent conductive network, which can well meet the performance requirements of the negative electrode sheet in the lithium ion battery, thereby helping to improve the cycle, rate and other performances of the lithium ion battery; it can be seen from the above mass ratio that the amount of conductive agent in the negative electrode slurry of the present invention is relatively small, which means that only a small amount of conductive agent is needed in the negative electrode slurry of the present invention to effectively achieve the effective coating of the hard silicon-based particles by the conductive agent, thereby effectively ensuring a good conductive network of the negative electrode sheet.
[0033] In another aspect of the present invention, the present invention provides a method for preparing the negative electrode slurry described above. According to an embodiment of the present invention, the method for preparing the negative electrode slurry comprises:
[0034] S10: performing a first mixing of the hard silicon-based particles, the granular conductive agent, the linear conductive agent, the binder and the solvent to obtain a mixed slurry.
[0035] According to some embodiments of the present invention, the method for obtaining the mixed slurry includes:
[0036] S11: preparing a linear conductive agent into a linear conductive paste.
[0037] In this step, there is no special requirement for the specific configuration method of the linear conductive paste, and those skilled in the art can prepare it according to conventional technical means in the art, for example, the linear conductive agent can be mixed with an appropriate amount of dispersant, water, etc.
[0038] Wherein, the linear conductive agent includes at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes, that is, the linear conductive paste is single-walled carbon nanotube paste, multi-walled carbon nanotube paste or a mixture of the two. Wherein, in the linear conductive paste, the average length of the single-walled carbon nanotube is 5μm to 15μm, such as 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, etc., and the average length of the multi-walled carbon nanotube is 5μm to 30μm, such as 5μm, 7μm, 10μm, 12μm, 15μm, 18μm, 20μm, 22μm, 25μm, 27μm, 30μm, etc. The carbon nanotubes with the above length requirements can be well wrapped with hard silicon-based particles. If the length is shorter, it will make it difficult for the carbon nanotubes to wrap the hard silicon-based particles.
[0039] S12: Mixing the binder and the solvent to prepare a binder glue solution.
[0040] In this step, the concentration of the binder glue can be 1% to 40%, such as 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, etc. Those skilled in the art can flexibly design the concentration of the binder glue within the above range according to the specific situation, or purchase it on the market. In this way, a negative electrode slurry with suitable viscosity can be obtained, which is convenient for coating and conducive to a negative electrode sheet with good performance such as good conductivity. Among them, the solvent can be water.
[0041] S13: Mix and stir the hard silicon-based particles, the granular conductive agent, the linear conductive slurry, the binder glue and the solvent to obtain a mixed slurry, wherein the solvent may be water.
[0042] According to some embodiments of the present invention, the solid content of the mixed slurry is 25% to 60%, and the solid content of the mixed slurry is 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, etc. Therefore, when preparing the negative electrode sheet, the mixed slurry with the above solid content is easier to form a film, which helps to improve the overall performance of the negative electrode sheet, such as thickness uniformity, conductivity and other properties. If the solid content of the mixed slurry is too small and the fluidity of the mixed slurry is large, the slurry flow during the coating process will cause uneven film; if the solid content is too large and the fluidity of the mixed slurry is poor, the film uniformity during the coating process is also poor, and even the film is cracked.
[0043] Furthermore, in some embodiments, during the preparation of the mixed slurry, the mixing and stirring time is 5 min to 60 min, and the rotation speed can be 100 rpm to 1000 rpm. Under the above conditions, a uniformly mixed mixed slurry can be prepared in a short time.
[0044] S20: performing a second mixing on the mixed slurry under a predetermined pressure to obtain a negative electrode slurry.
[0045] In some embodiments of the present invention, the predetermined pressure is 3000psi to 30000psi, for example, 3000psi, 4000psi, 5000psi, 7000psi, 9000psi, 10000psi, 11000psi, 12000psi, 13000psi, 14000psi, 15000psi, 20000psi, 25000psi, 30000psi, etc. Under the above pressure, the hard silicon-based particles can effectively collide with each other to disperse the particles that are about to undergo secondary agglomeration, so as to avoid secondary agglomeration, and form a very uniform three-dimensional conductive network between the granular conductive agent and the linear conductive agent. This three-dimensional conductive network has a good wrapping effect on the hard silicon-based particles, further improving the conductivity of the slurry, and at the same time effectively inhibiting the expansion of the hard silicon-based particles; at the same time, the collision under the above pressure will not cause damage to the hard silicon-based particles themselves and other components such as the conductive agent; if the pressure is too low, the hard silicon-based particles cannot form a good mutual collision, and in the second mixing process, some of the granular conductive agents will still undergo secondary agglomeration, affecting the uniformity of the conductive agent dispersion; if the pressure is too high, the collision between the hard silicon-based particles will cause the hard silicon-based particles to be destroyed, so that the performance of the active material hard silicon-based particles is not fully exerted, thereby affecting the conductivity of the negative electrode sheet and the cycle, rate and other performance of the lithium-ion battery.
[0046] In some embodiments of the present invention, the second mixing can be achieved by a high-pressure homogenization method, that is, the granular conductive agent and the linear conductive agent are evenly distributed on the surface of the hard silicon-based particles by the high-pressure homogenization method, forming a very uniform three-dimensional conductive network. This three-dimensional conductive network has a good wrapping effect on the silicon-based active material, further improving the conductivity of the slurry, reducing the amount of conductive agent added, and at the same time inhibiting the expansion of the hard silicon-based particles, thereby improving the rate and cycle performance of the lithium-ion battery.
[0047] According to an embodiment of the present invention, in the above-mentioned method for preparing negative electrode slurry, during the second mixing process of the mixed slurry, the mutual collision between the hard silicon-based particles can effectively inhibit the secondary agglomeration problem of the granular conductive agent caused by the van der Waals force, or the mutual collision between the hard silicon-based particles can knock and scatter the particles that have undergone secondary agglomeration, thereby making the granular conductive agent evenly adhere to the surface of the linear conductive agent, and the granular conductive agent and the linear conductive agent both form a uniform phase wrapped on the surface of the hard silicon-based particles, thereby forming a uniform three-dimensional conductive network, and at the same time effectively inhibiting the expansion of the hard silicon-based particles, thereby improving the conductive properties of the negative electrode slurry; and since the agglomeration of the granular conductive agent is avoided, a small amount of conductive agent can be used to wrap the surface of the hard silicon-based particles, that is, the above-mentioned technical scheme of the present invention can further reduce the amount of conductive agent used, while improving the cycle, rate and other performances of the lithium-ion battery using the negative electrode slurry. Furthermore, the above-mentioned method is simple and easy to implement, has high efficiency, and is convenient for industrial production and management.
[0048] In another aspect of the present invention, the present invention provides a negative electrode sheet. According to an embodiment of the present invention, the negative electrode sheet is prepared from the negative electrode slurry described above. Therefore, the negative electrode sheet of the present invention has good conductivity and effectively suppresses the expansion of hard silicon-based particles, thereby helping to improve the cycle, rate and other performances of the lithium-ion battery using the negative electrode sheet. It can be understood by those skilled in the art that the negative electrode sheet has all the features and advantages of the negative electrode slurry described above, and no further elaboration is given here.
[0049] In the embodiments of the present invention, there are no special requirements for the specific method of preparing the negative electrode sheet from the negative electrode slurry, and those skilled in the art can flexibly select it according to the existing technical means and actual needs. In some embodiments, the negative electrode slurry can be coated on the surface of the negative electrode collector (such as copper foil), and after drying, rolling and other processes, a negative electrode sheet with a certain thickness is formed.
[0050] in,
[0051] In another aspect of the present invention, the present invention provides a lithium ion battery. According to an embodiment of the present invention, the lithium ion battery includes the negative electrode sheet described above. Therefore, the lithium ion battery of the present invention has better cycle and rate performance. It can be understood by those skilled in the art that the lithium ion battery has all the features and advantages of the negative electrode slurry described above, and no further details will be given here.
[0052] Those skilled in the art can understand that, in addition to the above-mentioned negative electrode sheet, the lithium-ion battery also has the necessary structures of a conventional lithium-ion battery, for example, it also includes a negative electrode shell, a positive electrode sheet, an electrolyte, a diaphragm, a gasket, a positive electrode shell and other structures.
[0053] Example
[0054] Example 1
[0055] The raw materials are: hard silicon-based particles, granular conductive agent, linear conductive agent, and binder are SiO x @C, SuperP, single-walled carbon nanotubes, styrene-butadiene rubber and sodium carboxymethyl cellulose, the mass ratio of which is 93:3.5:0.5:2:1, SiO x The particle size D50 of @C particles is 5 μm and the hardness is 106 HV. The steps of preparing the negative electrode slurry are as follows:
[0056] (1) dispersing single-walled carbon nanotubes in an aqueous solution of sodium carboxymethyl cellulose to form a single-walled carbon nanotube conductive slurry, wherein the dispersed single-walled carbon nanotubes have an average length of 10 μm;
[0057] (2) dissolving sodium carboxymethyl cellulose in water to form a sodium carboxymethyl cellulose emulsion with a concentration of 1.5%, and dissolving styrene-butadiene rubber in water to form a styrene-butadiene rubber emulsion with a concentration of 40%;
[0058] (3) SiO x @C, Super P, the single-walled carbon nanotube slurry obtained in step (1), 1.5% sodium carboxymethyl cellulose obtained in step (2), 40% styrene-butadiene rubber latex and an appropriate amount of water were mixed, and stirred at 250 rpm for 15 min to obtain a mixed slurry, wherein the solid content of the mixed slurry was 45%;
[0059] (4) The mixed slurry obtained in step (3) is further mixed at a pressure of 4000 psi to obtain a negative electrode slurry that can be directly coated.
[0060] Example 2
[0061] The raw materials are: hard silicon-based particles, granular conductive agent, linear conductive agent, and binder are SiO x @C, SuperP, acetylene black, single-walled carbon nanotubes, styrene-butadiene rubber and sodium carboxymethyl cellulose, the mass ratio of which is 93:2:1.5:0.5:2:1, SiO x The particle size D50 of @C particles is 5 μm and the hardness is 106 HV. The steps of preparing the negative electrode slurry are as follows:
[0062] (1) dispersing single-walled carbon nanotubes in an aqueous solution of sodium carboxymethyl cellulose to form a single-walled carbon nanotube conductive slurry, wherein the dispersed single-walled carbon nanotubes have an average length of 10 μm;
[0063] (2) dissolving sodium carboxymethyl cellulose in water to form a sodium carboxymethyl cellulose emulsion with a concentration of 1.5%, and dissolving styrene-butadiene rubber in water to form a styrene-butadiene rubber emulsion with a concentration of 40%;
[0064] (3) SiO x @C, Super P, acetylene black, the single-walled carbon nanotube slurry obtained in step (1), 1.5% sodium carboxymethyl cellulose obtained in step (2), 40% styrene-butadiene rubber latex and an appropriate amount of water were mixed, and stirred at 300 rpm for 10 minutes to obtain a mixed slurry, wherein the solid content of the mixed slurry was 48%;
[0065] (4) The mixed slurry obtained in step (3) is further mixed at a pressure of 6000 psi to obtain a negative electrode slurry that can be directly coated.
[0066] Example 3
[0067] The raw materials are: hard silicon-based particles, granular conductive agent, linear conductive agent, and binder are respectively micron Si, SuperP, single-walled carbon nanotubes and polyacrylic acid, and the mass ratio is 95:2.5:0.5:2. The particle size D50 of the micron Si particles is 7.5μm and the hardness is 71HV. The steps of the preparation method of the negative electrode slurry are as follows:
[0068] (1) dispersing single-walled carbon nanotubes in an aqueous solution of sodium carboxymethyl cellulose to form a single-walled carbon nanotube conductive slurry, wherein the dispersed single-walled carbon nanotubes have an average length of 10 μm;
[0069] (2) dissolving polyacrylic acid in water to form a polyacrylic acid glue solution with a concentration of 8%;
[0070] (3) mixing micron Si, Super P, the single-walled carbon nanotube slurry obtained in step (1), the 8% polyacrylic acid glue obtained in step (2) and an appropriate amount of water, and stirring at 300 rpm for 15 min to obtain a mixed slurry, wherein the solid content of the mixed slurry is 40%;
[0071] (4) The mixed slurry obtained in step (3) is further mixed at a pressure of 4500 psi to obtain a negative electrode slurry that can be directly coated.
[0072] Example 4
[0073] The raw materials are: hard silicon-based particles, granular conductive agent, linear conductive agent, and binder are respectively micron Si, SuperP, single-walled carbon nanotubes, multi-walled carbon nanotubes, and polyacrylic acid, and the mass ratio is 95:2.5:0.3:0.2:2. The particle size D50 of the micron Si particles is 7.5μm and the hardness is 71HV. The steps of the preparation method of the negative electrode slurry are as follows:
[0074] (1) dispersing single-walled carbon nanotubes in an aqueous solution of sodium carboxymethyl cellulose to form a single-walled carbon nanotube conductive slurry, wherein the dispersed single-walled carbon nanotubes have an average length of 10 μm, and dispersing multi-walled carbon nanotubes in an aqueous solution of sodium carboxymethyl cellulose to form a multi-walled carbon nanotube conductive slurry, wherein the dispersed multi-walled carbon nanotubes have an average length of 15 μm;
[0075] (2) dissolving polyacrylic acid in water to form a polyacrylic acid glue solution with a concentration of 8%;
[0076] (3) mixing micron Si, Super P, the single-walled carbon nanotube slurry and multi-walled carbon nanotube conductive slurry obtained in step (1), the 8% polyacrylic acid glue obtained in step (2) and an appropriate amount of water, and stirring at 200 rpm for 15 minutes to obtain a mixed slurry, wherein the solid content of the mixed slurry is 50%;
[0077] (4) The mixed slurry obtained in step (3) is further mixed at a pressure of 8000 psi to obtain a negative electrode slurry that can be directly coated.
[0078] Example 5
[0079] The raw materials are: hard silicon-based particles, granular conductive agent, linear conductive agent, and binder are respectively micron Si, SuperP, single-walled carbon nanotubes, multi-walled carbon nanotubes, and polyacrylic acid, and the mass ratio is 95:2.5:0.3:0.2:2. The particle size D50 of the micron Si particles is 7.5μm and the hardness is 71HV. The steps of the preparation method of the negative electrode slurry are as follows:
[0080] (1) dispersing single-walled carbon nanotubes in an aqueous solution of sodium carboxymethyl cellulose to form a single-walled carbon nanotube conductive slurry, wherein the dispersed single-walled carbon nanotubes have an average length of 10 μm, and dispersing multi-walled carbon nanotubes in an aqueous solution of sodium carboxymethyl cellulose to form a multi-walled carbon nanotube conductive slurry, wherein the dispersed multi-walled carbon nanotubes have an average length of 15 μm;
[0081] (2) dissolving polyacrylic acid in water to form a polyacrylic acid glue solution with a concentration of 8%;
[0082] (3) Mix the micron Si, Super P, the single-walled carbon nanotube slurry and the multi-walled carbon nanotube conductive slurry obtained in step (1), the 8% polyacrylic acid glue obtained in step (2) and an appropriate amount of water, and stir at 200 rpm for 15 minutes to obtain a mixed slurry, wherein the solid content of the mixed slurry is 50%.
[0083] Comparative Example 1
[0084] The raw materials are: silicon-based particles, granular conductive agent, linear conductive agent, and binder are non-hard SiO x@C, Super P, single-walled carbon nanotubes, styrene-butadiene rubber and sodium carboxymethyl cellulose, the mass ratio of which is 93:3.5:0.5:2:1, non-hard SiO x The particle size D50 of @C particles is 5 μm and the hardness is 5 HV. The steps for preparing the negative electrode slurry are as follows:
[0085] (1) dispersing single-walled carbon nanotubes in an aqueous solution of sodium carboxymethyl cellulose to form a single-walled carbon nanotube conductive slurry, wherein the dispersed single-walled carbon nanotubes have an average length of 10 μm;
[0086] (2) dissolving sodium carboxymethyl cellulose in water to form a sodium carboxymethyl cellulose emulsion with a concentration of 1.5%, and dissolving styrene-butadiene rubber in water to form a styrene-butadiene rubber emulsion with a concentration of 40%;
[0087] (3) Non-hard SiO x @C, Super P, the single-walled carbon nanotube slurry obtained in step (1), 1.5% sodium carboxymethyl cellulose obtained in step (2), 40% styrene-butadiene rubber and an appropriate amount of water were mixed, and stirred at 250 rpm for 15 minutes to obtain a mixed slurry, wherein the solid content of the mixed slurry was 45%;
[0088] (4) The mixed slurry obtained in step (3) is further mixed at a pressure of 4000 psi to obtain a negative electrode slurry that can be directly coated.
[0089] Comparative Example 2
[0090] The raw materials are: silicon-based particles, granular conductive agent, linear conductive agent, and binder are non-hard micron Si, Super P, single-walled carbon nanotubes, multi-walled carbon nanotubes, and polyacrylic acid, respectively, and the mass ratio is 95:2.5:0.3:0.2:2. The particle size D50 of the non-hard micron Si particles is 7.5μm and the hardness is 2HV. The steps of the preparation method of the negative electrode slurry are as follows:
[0091] (1) dispersing single-walled carbon nanotubes in an aqueous solution of sodium carboxymethyl cellulose to form a single-walled carbon nanotube conductive slurry, wherein the dispersed single-walled carbon nanotubes have an average length of 10 μm, and dispersing multi-walled carbon nanotubes in an aqueous solution of sodium carboxymethyl cellulose to form a multi-walled carbon nanotube conductive slurry, wherein the dispersed multi-walled carbon nanotubes have an average length of 15 μm;
[0092] (2) dissolving polyacrylic acid in water to form a polyacrylic acid glue solution with a concentration of 8%;
[0093] (3) Mixing non-hard micron Si, Super P, the single-walled carbon nanotube slurry and multi-walled carbon nanotube conductive slurry obtained in step (1), the 8% polyacrylic acid glue obtained in step (2) and an appropriate amount of water, and stirring at 200 rpm for 15 minutes to obtain a mixed slurry, wherein the solid content of the mixed slurry is 50%;
[0094] (4) The mixed slurry obtained in step (3) is further mixed at a pressure of 8000 psi to obtain a negative electrode slurry that can be directly coated.
[0095] Performance Testing:
[0096] (1) Testing of hardness of silicon-based particles: Use a micro Vickers hardness tester to measure 3-5 values of the powder and then calculate the average value, which is the hardness value of the silicon-based particles in the above embodiment.
[0097] (2) Volume resistivity: According to GB / T33813-2017 standard, the obtained silicon-based negative electrode slurry was coated on a PET film. After drying, the film was cut and pressed at 10t pressure for 5 min. The volume resistivity of the sample was then tested using a four-probe resistivity tester. The test results are shown in Table 1.
[0098] Table 1
[0099] Volume resistivity (Ω·cm) Example 1 0.258 Example 2 0.263 Example 3 0.281 Example 4 0.278 Example 5 0.381 Comparative Example 1 0.392 Comparative Example 2 0.430
[0100] It can be seen from Table 1 that the volume resistivity of the electrode sheet obtained by the negative electrode slurry preparation method provided by the present invention is relatively low. x @C particles and applying 4000psi pressure to the mixed slurry to prepare the silicon-based negative electrode slurry, the pole piece volume resistivity is 0.258Ω·cm. x @C particles and the same pressure are applied to the silicon-based negative electrode slurry, and its pole piece volume resistivity is 0.392Ω·cm; Example 4 uses hard micron Si particles and applies 8000psi pressure to the mixed slurry to prepare the silicon-based negative electrode slurry, and its pole piece volume resistivity is 0.278Ω·cm, and the corresponding comparative example 2 uses non-hard micron Si particles and applies the same pressure to prepare the silicon-based negative electrode slurry, and its pole piece volume resistivity is 0.430Ω·cm; further, by comparing Examples 4 and 5, it can be further found that further pressurizing and mixing the mixed slurry can further reduce the volume resistivity of the negative electrode slurry, that is, improve the conductivity of the negative electrode slurry. Similarly, according to the test data, it can be seen that Examples 2 and 3 also have lower volume resistivity.
[0101] In summary, the silicon-based negative electrode slurry prepared by the method of using hard silicon-based particles and applying pressure to the mixed slurry to cause collisions between the hard particles has a lower volume resistivity of the electrode sheet. The reason is that in the process of applying pressure, more effective collisions occur between the hard particles, which better inhibits the secondary agglomeration of the granular conductive agent due to van der Waals forces, and then the granular conductive agent and the linear conductive agent form a uniform three-dimensional conductive network wrapped on the surface of the hard silicon-based particles. Therefore, the silicon-based negative electrode slurry prepared by this method has a lower resistivity and the conductivity of the negative electrode sheet is better.
[0102] The negative electrode sheets obtained by the negative electrode slurry preparation methods in Example 1 and Comparative Example 1 were tested by scanning electron microscope, and the test results are shown in Figure 1 and Figure 2 ,Depend on Figure 1 It can be seen that the granular conductive agent in the negative electrode sheet prepared by the slurry obtained in Example 1 did not reagglomerate in the gaps between the hard silicon-based particles, but the granular conductive agent and the linear conductive agent were uniformly wrapped on the surface of the hard silicon-based particles to form a good conductive network. At the same time, the linear conductive agent formed a good wrapping around the hard silicon-based particles and also suppressed their volume expansion. Figure 2 It can be seen that in the negative electrode sheet prepared by the slurry obtained in Comparative Example 1, the granular conductive agent is secondary agglomerated in the gaps between the hard silicon-based particles. At the same time, the secondary agglomeration of the granular conductive agent affects the dispersion of the linear conductive agent, that is, the linear conductive agent is also dispersed in the gaps between the hard silicon-based particles. This indicates that the linear conductive agent fails to wrap the hard silicon-based particles, that is, it cannot inhibit their volume expansion.
[0103] (3) Cycle performance: The prepared silicon-based negative electrode slurry was directly coated on copper foil, and after drying, it was punched into electrode sheets with a diameter of 12 mm using a slicer, and assembled into lithium half-cell button batteries in a glove box. The battery assembly order was negative electrode shell, lithium sheet, separator (PP), electrode sheet, electrolyte, gasket, spring sheet, positive electrode shell, and tested using the Blue Electric Battery Test System CT3001C. The test temperature was room temperature, the charge and discharge voltage range was 0.005V~2V, and a long cycle test was performed at a current of 0.2C. The specific results are shown in Table 2. The cycle performance test results of the button batteries assembled with the electrode sheets after coating with the two silicon-based negative electrode slurries prepared in Example 1 and Comparative Example 1 can be found in Table 2. Figure 3 .
[0104] Table 2
[0105] First discharge specific capacity (mAh / g) First efficiency (%) Example 1 1828.2 77.75 Example 2 1681.18 77.41 Example 3 1632.98 91.63 Example 4 1713.59 90.73 Example 5 1658.31 90.32 Comparative Example 1 1272.98 75.84 Comparative Example 2 1549.77 90.01
[0106] (4) Rate performance: The button cell assembled above was subjected to rate performance test using the Blue Power Battery Test System CT3001C, wherein the test temperature was room temperature, the charge and discharge voltage range was 0.005 V to 2 V, and the rate test was performed at 0.1C, 0.2C, and 0.5C for 5 cycles (with 0.1C as the benchmark). The specific results are shown in Table 3. The rate performance test results of the button cell assembled after the two silicon-based negative electrode slurries prepared in Example 1 and Comparative Example 1 are shown in Table 3. Figure 4 .
[0107] Table 3
[0108] First discharge specific capacity (mAh / g) First efficiency (%) Example 1 1798.01 79.54 Example 2 1840.49 79.14 Example 3 1816.15 90.18 Example 4 1658.25 91.13 Example 5 1607.33 90.08 Comparative Example 1 1570.59 79.01 Comparative Example 2 1557.77 89.93
[0109] According to Table 2, Table 3, Figure 3 , Figure 4 It can be seen that the button-type battery cycle and rate performance of the button-type battery assembled after the electrode piece is coated with the silicon-based negative electrode slurry prepared in Example 1 of the present invention are better than those of Comparative Example 1, and the button-type battery cycle and rate performance of the button-type battery assembled after the electrode piece is coated with the silicon-based negative electrode slurry prepared in Example 4 are better than those of Comparative Example 2. Specifically, in the cycle performance test, the first discharge specific capacity of Example 1 is 1828.2 mAh / g, while the first discharge specific capacity of Comparative Example 1 is 1272.98 mAh / g, and in the rate performance test, the first discharge specific capacity of Example 1 is 1798.01 mAh / g, while the first discharge specific capacity of Comparative Example 1 is 1570.59 mAh / g; in the cycle performance test, the first discharge specific capacity of Example 4 is 1713.59 mAh / g, while the first discharge specific capacity of Comparative Example 2 is 1549.77 mAh / g, and in the rate performance test, the first discharge specific capacity of Example 4 is 1658.25 mAh / g, while the first discharge specific capacity of Comparative Example 2 is 1557.77 mAh / g. It can be seen that the silicon-based negative electrode slurries prepared in Examples 1 and 4 and Examples 2 and 3 have excellent three-dimensional conductive networks, thereby improving the cycle and rate performance of the lithium-ion battery. By comparing Examples 4 and 5, it can be seen that the first discharge specific capacity of Example 4 is also better than that of Example 5, that is, the cycle performance and rate performance of the lithium-ion battery obtained in Example 4 are better than those of the lithium-ion battery obtained in Example 5.
[0110] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0111] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0112] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A negative electrode slurry, characterized in that: include: Hard silicon-based particles, a granular conductive agent, a linear conductive agent, a binder and a solvent, wherein the hardness of the hard silicon-based particles is 50 HV to 200 HV.
2. The negative electrode slurry according to claim 1, characterized in that The particle size D50 of the hard silicon-based particles is 3 μm to 10 μm.
3. The negative electrode slurry according to claim 1, characterized in that: The mass ratio of the hard silicon-based particles, the granular conductive agent, the linear conductive agent, and the binder is (80-98): (0.05-10): (0.001-1): (1-20).
4. The negative electrode slurry according to claim 1, characterized in that: The hard silicon-based particles are spherical or quasi-spherical.
5. The negative electrode slurry according to any one of claims 1 to 4, characterized in that: The hard silicon-based particles include SiO x At least one of @C, Si@C, Si / C, micron Si, SiO, and new silicon carbon; The granular conductive agent includes at least one of Super P, Ketjen black, acetylene black and graphite; The linear conductive agent includes at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes; The solvent is at least one of water or NMP.
6. A method for preparing the negative electrode slurry according to any one of claims 1 to 5, characterized in that: include: The hard silicon-based particles, the granular conductive agent, the linear conductive agent, the binder and the solvent are first mixed to obtain a mixed slurry; The mixed slurry is subjected to a second mixing process under a predetermined pressure to obtain the negative electrode slurry.
7. The method according to claim 6, characterized in that The predetermined pressure is 3000psi to 30000psi.
8. The method according to claim 6, characterized in that The solid content of the mixed slurry is 25% to 60%.
9. The method according to claim 6, characterized in that The method for obtaining the mixed slurry comprises: Formulating the linear conductive agent into a linear conductive slurry; Mixing the binder and the solvent to prepare a binder glue solution; The hard silicon-based particles, the granular conductive agent, the linear conductive slurry, the binder glue and the solvent are mixed and stirred to obtain the mixed slurry.
10. The method according to claim 9, characterized in that The linear conductive agent includes at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes, wherein In the linear conductive paste, the average length of the single-walled carbon nanotubes is 5 μm to 15 μm, and the average length of the multi-walled carbon nanotubes is 5 μm to 30 μm.
11. A negative electrode sheet, characterized in that: The negative electrode slurry is prepared from the negative electrode slurry according to any one of claims 1 to 5.
12. A lithium ion battery, characterized in that: Includes the negative electrode sheet as claimed in claim 11.
